2018
DOI: 10.1111/jfb.13605
|View full text |Cite
|
Sign up to set email alerts
|

Catch composition and aspects of the biology of sharks caught by Thai commercial fisheries in the Andaman Sea

Abstract: Catch composition, landing patterns and biological aspects of sharks caught by commercial fishing fleet operating in the Andaman Sea were recorded from landing sites in Ranong province of Thailand over a period of 1 year. Of the 64 species previously reported in the existing Thailand checklist, only 17 species were recorded in this study. Shark landings from the Andaman Sea appear now to be dominated largely by bamboo sharks Chiloscyllium spp. (Hemiscylliidae), which contribute c. 65% of the total number of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…A decrease in the diversity of species landed has also been documented in areas with high fishing pressure. Indeed, Thailand, closer to Andaman and Nicobar Islands than to mainland India, has recorded a decrease in landings of larger sharks from 41 species in 2004 to 15 species in 2014-15 [44]. Yet our results indicated that this is not yet the case in the Andaman and Nicobar Islands as four of the six dominantly landed sharks are larger bodied shark species.…”
Section: Discussionmentioning
confidence: 59%
“…A decrease in the diversity of species landed has also been documented in areas with high fishing pressure. Indeed, Thailand, closer to Andaman and Nicobar Islands than to mainland India, has recorded a decrease in landings of larger sharks from 41 species in 2004 to 15 species in 2014-15 [44]. Yet our results indicated that this is not yet the case in the Andaman and Nicobar Islands as four of the six dominantly landed sharks are larger bodied shark species.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, there is an ongoing targeted deep-sea shark fishery in the Andaman Islands that supplies the demand for shark liver oil [ 20 ]. Deep-sea sharks have rates of population increase that are on average less than half those of shelf and pelagic species and are some of the lowest levels recorded to date [ 42 ]. Population recovery rates also decrease with increasing depth, suggesting that these species are most susceptible to overexploitation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep-sea sharks have rates of population increase that are on average less than half those of shelf and pelagic species and are some of the lowest levels recorded to date [ 42 ]. Population recovery rates also decrease with increasing depth, suggesting that these species are most susceptible to overexploitation [ 42 ]. These life-history traits do not allow them to sustain intense fishing pressure which can lead to rapid population declines.…”
Section: Discussionmentioning
confidence: 99%
“…This record is constitute second record of M. owstoni in Indonesia after first record from Pelabuhan Ratu, West Java (Fahmi 2007). This species has not been recorded in Southeast Asian waters of the neighboring countries of Indonesia (Arunrugstichai et al 2018;Finucci & Duffy 2018; Arai & Azri 2019; Krajangdara 2019, Wildsingapore 2019), but it has been found in Australia and New Zealand (Last & Stevens 1994;Duffy 1997).…”
Section: Introductionmentioning
confidence: 99%